Dilemma in closing the bite: a case of orthognathic surgery. (1st January 2020) - Mehta, Siddharth; Kamath, Abhay T; Kudva, Adarsh; Srikanth, G; Urala, Arun
Abstract : This case report demonstrates treatment of an open bite case with a history of trauma to the maxillary anterior region in childhood. A 20-year-old adult male presented with a convex profile and significant anterior bite and unilateral posterior crossbite. Surgical bite correction was planned but posed a dilemma in the choice of surgery. CPD/Clinical Relevance: To demonstrate the outcome of a case of skeletal anterior open bite treated with orthognathic surgery.